Aesthetic Education In Fiction - Sayidov Murad (Zien Journals, 2022)
This article discusses the role of fiction in the educational process, particularly in aesthetic education. The works of some researchers are comparatively analyzed.
Keywords: literature; fiction; education; aesthetics